Effectiveness of home visiting on patients with hypertension: A systematic review and meta-analysis. Issue 10 (12th March 2021) - Ma, Yuxia; Lu, Hongmei; Zhang, Yuanyuan; Wang, Yutan; Li, Sijun; Yan, Fanghong; Han, Lin
Abstract: Background: Blood pressure lowering treatments can help prevent cardiovascular disease. However, little is known about the possibility of home visiting programs for hypertension. This study aims to evaluate the effectiveness of home visiting programs on hypertensive patients. Methods: We systematically reviewed the medical literature and performed a meta-analysis. Five electronic databases were systematically searched from their inception to September 2019. Two reviewers independently assessed the risk of bias of the studies included in the review using tools developed by the Cochrane Collaboration. The meta-analysis was performed using Review Manager software (version 5.3). Results: Thirteen RCTs with 2674 participants were identified. The home visiting program demonstrated a greater reduction in systolic blood pressure (MD = −5.63, 95% confidence interval (CI): −8.32 to −2.94), diastolic blood pressure (MD = −4.14, 95% CI: −6.72 to −1.56) and waist circumference (MD = −2.61, 95% CI: −3.5, −1.72) during a 6 month intervention. However, there were no significant differences between the groups in terms of body mass index, weight, or blood lipids. Conclusion: Home visiting programs were associated with improved BP control and reduced blood pressure, which indicate that it might be an effective method for management of hypertension. Abstract : Supplemental Digital Content is available in the text